The role of Education in Plato's Republic and Rousseau's Emile. - Melachrinou, Anna Maria (Tufts Archival Research Center, 2005)
In his own great treatise on education, Rousseau claimed that the Republic "is not at all a political work, as think those who judge books only by their titles. It is the most beautiful educational treatise every written." Rousseau and Plato demonstrate in their writings the importance of education in society and in the life of the individual. This thesis explores the role of education in Emile and the Republic and looks into the similarities and differences between the two thinkers. One of the strongest similarities is that both Plato and Rousseau claim that men live in chains and education can be the means to deal with them. While Rousseau attempts to legitimize the chains of society, Plato discusses the quest to break them. Based on this connection, my thesis analyzes the meaning, purpose, methods, and principles of education in each book. Rousseau and Plato attempt to build strong characters as the foundation to cultivate the intellect. They value the cultivation of comparative thinking and the contribution of education in the formation of citizens.